2019
DOI: 10.1016/s0140-6736(19)30474-x
|View full text |Cite|
|
Sign up to set email alerts
|

Drug-eluting or bare-metal stents for percutaneous coronary intervention: a systematic review and individual patient data meta-analysis of randomised clinical trials

Abstract: Background New-generation drug-eluting stents (DES) have been mostly investigated by means of head-to-head non-inferiority trials, which typically showed comparable efficacy and greater safety as compared with early-generation DES. Evidence related to new-generation DES versus bare-metal stents (BMS) is more limited, and there remain uncertainties on their comparative safety profile. Methods We performed an individual patient data (IPD) meta-analysis of randomized trials comparing new-generation DES with BMS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
119
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 28 publications
3
119
2
2
Order By: Relevance
“…Early-generation 17,18 and newer-generation drug-eluting stents 2 have progressively improved safety and efficacy outcomes compared with bare-metal stents in patients with acute STEMI undergoing primary PCI. Newer-generation drug-eluting stents that combine thin strut stent platforms with biocompatible durable polymer coatings were associated with further reductions in the risk of repeat revascularisation and stent thrombosis after primary PCI compared with early-generation thicker strut durable polymer drug-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…Early-generation 17,18 and newer-generation drug-eluting stents 2 have progressively improved safety and efficacy outcomes compared with bare-metal stents in patients with acute STEMI undergoing primary PCI. Newer-generation drug-eluting stents that combine thin strut stent platforms with biocompatible durable polymer coatings were associated with further reductions in the risk of repeat revascularisation and stent thrombosis after primary PCI compared with early-generation thicker strut durable polymer drug-eluting stents.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials have demonstrated that DCB is associated with comparable angiographic results and clinical events with rst-generation DES [17,18]. EES was a second-generation DES, which was superior to BMS and rst-generation DES in reducing the risk of stent thrombosis and repeat revascularization [1,19]. Several trials compared DCB with EES for the treatment of ISR, but they had small sample sizes and inconsistent outcomes [4,5,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In-stent restenosis (ISR) is one of the main stumbling blocks for stent implantation in patients with coronary artery disease [1]. Although the medicines and stents had advanced prominently, ISR was still remarkable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early technical success and a operator‐friendly feature is not enough. Before implementation in routine practice, it will be important to know whether this technology is at least non‐inferior to current, highly performing, new‐generation drug‐eluting stents …”
mentioning
confidence: 99%